Light signal regulates endoreduplication and tomato fruit expansion through the SlPIF1a-SlTLFP8-SlCDKB2 module - Jiaojiao Zhang; Jiayi Xu; Xinman Wang; Ying Liu; Shuangtao Li; Jialong Zhang; Lingfeng He; Luqin Guo; Chonghua Li; Xin-Xu Li; Yang-Dong Guo; Na Zhang (Proceedings of the National Academy of Sciences, 2025)
Light serves as an energy source for cell division and expansion during fruit development. Cell expansion significantly influences fruit size and is closely linked to endoreduplication, a unique cell cycle variation characterized by DNA replication without cytokinesis. Paradoxically, under conditions of ample photosynthates, light signaling suppresses cell expansion. The intricate regulation of endoreduplication in response to light signaling during fruit development has remained an intriguing question. Here, our study revealed that Tubby-like F-box protein 8 (SlTLFP8) orchestrated endoreduplication to facilitate fruit cell expansion. As an Skp1-Cullin-F-box (SCF)-type E3 ligase, SlTLFP8 promoted the ubiquitination and subsequent degradation of CYCLIN-DEPENDENT KINASE B2 (SlCDKB2), thereby elevating DNA ploidy. The light signaling component PHYTOCHROME-INTERACTING FACTOR 1a (SlPIF1a), identified as a pivotal negative regulator in the plant’s light response, was found to directly interact with the promoter of the SlTLFP8 gene, thereby stimulating its transcriptional activation. Indeed, SlPIF1a contributed to a faster expansion rate of tomato fruit during nighttime. Altogether, our results elucidate the connection between light signals and fruit size regulation through endoreduplication.